TARAXACUM OFFICINALE L. IMPORTANCE OF THE PLANT IN FOLK MEDICINE AND MEDICAL USE (Modern American Journal of Medical and Health Sciences, 2025)
This article analyzes the importance of Taraxacum officinale L. (dandelion) in folk medicine and the directions of its use in medicine. Dandelion has long been used as a diuretic, blood purifier, and a means of improving the functioning of the liver and biliary tract. According to the results of modern research, it contains phenolic compounds, flavonoids, triterpenes, inulin, vitamins (A, C, E) and mineral elements (K, Ca, Fe, Mg), which have antioxidant, anti-inflammatory, hepatoprotective and immunomodulatory effects. In medicine, extracts of Taraxacum officinale are widely used in the form of phytopreparations, biologically active additives, tonic and detoxifying syrups, and tea mixtures. The results of the study confirm that this plant is an important scientific basis for the development of a new generation of phytopreparations based on natural, safe and highly biologically effective components.